2002
DOI: 10.1128/aem.68.9.4187-4193.2002
|View full text |Cite
|
Sign up to set email alerts
|

Tissue Localization of the Endosymbiotic Bacterium “ Candidatus Blochmannia floridanus” in Adults and Larvae of the Carpenter Ant Camponotus floridanus

Abstract: The distribution of endosymbiotic bacteria in different tissues of queens, males, and workers of the carpenter ant Camponotus floridanus was investigated by light and electron microscopy and by in situ hybridization. A large number of bacteria could be detected in bacteriocytes within the midguts of workers, young virgin queens, and males. Large amounts of bacteria were also found in the oocytes of workers and queens. In contrast, bacteria were not present in oocyte-associated cells or in the spermathecae of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
106
1

Year Published

2003
2003
2013
2013

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 81 publications
(113 citation statements)
references
References 16 publications
6
106
1
Order By: Relevance
“…To investigate a possible role of Blochmannia at the colony level, experiments were carried out with animals treated with rifampin, which, as previously described, causes a strong decrease of the bacterial load in treated animals (19). Confirming the previous results, rifampin treatment did not interfere significantly with the viability of the adult workers and no obvious toxic effect on these animals could be noted.…”
Section: Resultsmentioning
confidence: 60%
See 2 more Smart Citations
“…To investigate a possible role of Blochmannia at the colony level, experiments were carried out with animals treated with rifampin, which, as previously described, causes a strong decrease of the bacterial load in treated animals (19). Confirming the previous results, rifampin treatment did not interfere significantly with the viability of the adult workers and no obvious toxic effect on these animals could be noted.…”
Section: Resultsmentioning
confidence: 60%
“…Subsequently, the mother colony (including the queen and thus all brood produced by the queen) and one of the worker groups were treated with the antibiotic rifampin (C 43 H 58 N 4 O 12 ; Serva Elektrophorese GmbH); the other worker group, used as a control, was not. The antibiotic was fed to the ants twice a week over a period of 13 weeks in a solution containing 1% rifampin, 49.5% water, and 49.5% honey (wt/wt) as described previously (19). Workers that died were not replaced with workers from the mother colony, and thus the numbers of workers in the subcolonies decreased steadily during the experimental period.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For hybridization within the antennae, fresh antennae from female beewolves were cut into sections with a razor blade and glued onto microscope slides. Fixation and pre-treatment of the samples was performed following a previously described protocol (Sauer et al, 2002). Hybridization was carried out as for the bacterial samples, but with 3 h incubation with the labelled probe.…”
Section: Methodsmentioning
confidence: 99%
“…generally feed on a complex diet composed of dead and alive insects, bird excrement, and sweet food wastes. Despite their complex diet, these animals are endowed with bacterio-cytes carrying obligate intracellular bacteria of the genus "Candidatus Blochmannia" (10,104,105,109). On the other hand, a recent survey of ants living in tropical rain forest canopies has shown that at least in this geographical region, ants, including many Camponotus species, can be considered to be "secondary herbivores" since they may feed mainly on plant or insect exudates and are not predators or scavengers (24).…”
Section: Physiological Significance Of Endosymbiotic Bacteria For Thementioning
confidence: 99%